Relationship between mental toughness and sport performance among contact and non-contact sport athletes / Mardiana Mazaulan - Mazaulan, Mardiana (2013)
The purpose this study was to determine the relationship between mental toughness and sport performance among contact sport and non-contact sport athletes. It was also done to compare difference of mental toughness dimension between contact sport and non-contact sport athletes and difference of mental toughness between genders. It was hypothesized that there was a relationship between mental toughness and level o f athletes’ achievement among athletes. 285 athletes from SUKOB competition (males = 147, females =138) aged 18 to 26 years old participated in this study. The methods involved in this study was self evaluation by the participants themtself. Questionnaire was distributed to the athletes that participates the event during that time. After finish the match the researcher was evaluated the sport performance based on the result of the mach either win or lose. Findings this current study showed a significant, weak and negative relationship between overall mental toughness and sport performance among contact and non-contact sports athletes (r=-.398, p=.000). Contact sport athletes score higher in overall mental toughness compare with non-contact sport athletes (f=2.99, p=.003). A significant, weak and positive relationship between highest level of athletes achievement and overall mental toughness (r=. 197,/?=.001) also can be found in this study. It also showed male athletes score high level of mental toughness in overall mental toughness <7=2.05, p= 0.41) It can be concluded that mental toughness is important component in psychological skills that should be add during training session to improved and get an excellent performance in competition.